Synthesis, anticancer evaluation and molecular docking studies of new benzimidazole- 1,3,4-oxadiazole derivatives as human topoisomerase types I poison - Ulviye Acar Çevik; Begüm Nurpelin Sağlık; Derya Osmaniye; Serkan Levent; Betül Kaya Çavuşoğlu; Abdullah Burak Karaduman; Özlem Atlı Eklioğlu; Yusuf Özkay; Zafer Asım Kaplancıklı (Taylor & Francis Group, 2020)
In this study, some benzimidazole-oxadiazole derivatives were synthesised and tested for their in vitro anticancer activities on five cancer cell lines, including HeLa, MCF7, A549, HepG2 and C6. Their structures were elucidated by IR, 1H-NMR, 13C-NMR, 2 D-NMR and HRMS spectroscopic methods. Among all screened compounds; 5a, 5b, 5d, 5e, 5k, 5l, 5n and 5o exhibited potent selective cytotoxic activities against various tested cancer cell lines. Especially, compounds 5l and 5n exhibited the most antiproliferative activity than Hoechst 33342 and doxorubicin against HeLa cell line, with IC50 of 0.224 ± 0.011 µM and 0.205 ± 0.010 µM, respectively. Furthermore, these potent lead cytotoxic agents were evaluated in terms of their inhibition potency against Topoisomerase I and it was determined that selected compounds inhibited the Topoisomerase I. Docking studies were performed and probable interactions in the DNA-Topo I enzyme complex was determined.